Rekonsiliasi Sebagai Proses Bersama Menyembuhkan Luka Sejarah Islam Kristen di Kota Ambon - Rachel Iwamony; Tri Astuti Relmasira (Religió: Jurnal Studi Agama-agama, 2017)
Reconciliation between Muslims and Christians in Ambon City is an important process to know and study. In 1999-2004 Muslims and Christians got involved in religious-based social conflicts. The social conflicts have uprooted their brotherhood and sisterhood relationship, and left deep historical wounds. However, after a decade, Muslims and Christians in Ambon City have been successful in restoring their life in harmony and peace. Based on the interview with young people in several areas in Ambon City, it was found that reconciliation could be restored by realizing that both Muslim and Christian people should restore the social conflicts for the sake of their good future. They have restored the reconciliation between themselves by having social and religious activities. The process of reconciliation and religious dialogue may be seen as ways of healing the historical wounds of the past social conflicts. [Rekonsiliasi antara Muslim dan Kristen di kota Ambon adalah sebuah proses penting untuk dikaji dan dipelajari. Pada tahun 1999-2004 Muslim dan Kristen terlibat dalam konflik sosial berlatarbelakang agama. Konflik sosial telah menghancurkan sendi-sendi hubungan persaudaraan mereka serta meninggalkan luka sejarah yang begitu dalam. Namun, setelah satu dekade, Muslim dan Kristen di kota Ambon telah berhasil memulihkan kehidupan mereka dalam keharmonisan dan kedamaian. Dengan mewawancarai kalangan muda di beberapa daerah di kota Ambon, terkuak bahwa rekonsiliasi terpulihkan dengan menyadari bahwa orang-orang Muslim dan Kristen akan memulihkan konflik sosial demi masa depan mereka yang lebih baik. Mereka telah mewujudkan rekonsiliasi melalui kegiatan sosial dan keagamaan. Proses rekonsiliasi dan dialog keagamaan dapat dilihat sebagai cara untuk menyembuhkan luka historis dari konflik sosial di masa lalu.]